2016
DOI: 10.1590/1982-0216201618521515
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da produção científica da apneia obstrutiva do sono na interface da fonoaudiologia

Abstract: The purpose of this study was to investigate the scientific production of Speech-Language Pathology and Audiology at the interface with Obstructive Sleep Apnea, considering impact factor, level of evidence and corresponding area of the Speech-Language Pathology and Audiology. A literature search was performed in databases Lilacs, PubMed and Scopus, through the intersection of keywords and specific free terms of Speech-Language Pathology and Audiology and "Sleep Apnea, Obstructive". For the article would be inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The articles included in this review have been published mainly in medicine, dentistry and physiology-focused journals, and only one of the studies was performed by speech-language therapists. The interface between speech-language pathology and sleep medicine is established mainly through myofunctional therapy 39 , and randomized controlled trials have shown promising and positive results in reducing the signs and symptoms in patients with OSA and in association with other treatment methods 35 , 36 , 37 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The articles included in this review have been published mainly in medicine, dentistry and physiology-focused journals, and only one of the studies was performed by speech-language therapists. The interface between speech-language pathology and sleep medicine is established mainly through myofunctional therapy 39 , and randomized controlled trials have shown promising and positive results in reducing the signs and symptoms in patients with OSA and in association with other treatment methods 35 , 36 , 37 , 40 .…”
Section: Discussionmentioning
confidence: 99%